2006
DOI: 10.1523/jneurosci.3157-05.2006
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating the Roles of the Hippocampus and Perirhinal Cortex in Processes beyond Long-Term Declarative Memory: A Double Dissociation in Dementia

Abstract: There is increasing evidence to suggest that the hippocampus and perirhinal cortex may mediate processes beyond long-term declarative memory. We assessed patients with Alzheimer's disease (AD) or semantic dementia (SD) on a visual oddity judgment task that did not place an explicit demand on long-term memory and is known to be sensitive to hippocampal and perirhinal cortex lesions. Importantly, within the medial temporal lobe, AD is associated with predominant hippocampal atrophy, whereas SD patients have grea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
139
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(159 citation statements)
references
References 36 publications
13
139
3
Order By: Relevance
“…Other criticisms of previous studies include the suggestion that because the oddity task used by others such as Buckley et al (2001) and Lee et al (2005Lee et al ( , 2006a) involved reward and/or repeated presentation of stimuli, learning across trials may occur in these paradigms and, therefore, deficits on these tasks may be interpreted as impairments in learning (Levy et al, 2005;Shrager et al, 2006;Squire et al, 2006). However, because the spontaneous oddity task used in the present study is a nonrewarded, single-trial paradigm, these criticisms do not apply to the present study.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Other criticisms of previous studies include the suggestion that because the oddity task used by others such as Buckley et al (2001) and Lee et al (2005Lee et al ( , 2006a) involved reward and/or repeated presentation of stimuli, learning across trials may occur in these paradigms and, therefore, deficits on these tasks may be interpreted as impairments in learning (Levy et al, 2005;Shrager et al, 2006;Squire et al, 2006). However, because the spontaneous oddity task used in the present study is a nonrewarded, single-trial paradigm, these criticisms do not apply to the present study.…”
Section: Discussionmentioning
confidence: 71%
“…This task was based on the automated oddity task developed by Buckley et al (2001), on which monkeys with PRh lesions were impaired. Oddity tasks have also been used to assess perceptual deficits in humans with MTL damage (Lee et al, 2005(Lee et al, , 2006a and have shown that damage including the PRh in humans, as in animals, impairs perceptual discrimination of nonspatial stimuli. In experiment 4 of the present study, we examined the performance of rats with lesions of PPRh or PRh and control rats in the simultaneous oddity discrimination task using four different levels of perceptual similarity.…”
Section: Discussionmentioning
confidence: 99%
“…Along with parahippocampal cortices, the hippocampus has been implicated in visual identification tasks, although the hippocampus may support more complex representations in this regard (Lee et al, 2005a(Lee et al, ,2005b(Lee et al, , 2006(Lee et al, , 2008. In the context of our experiment, we suggest that the hippocampus may form a representation that incorporates knowledge about the relevance/ predictability of the visual cues, which may then be used by other neural regions to control selection, such as the anterior parahippocampal cortex (Chelazzi et al, 1993(Chelazzi et al, , 1998.…”
Section: Discussionmentioning
confidence: 72%
“…This is concordant with single-unit work from Chelazzi and colleagues (Chelazzi et al, 1993(Chelazzi et al, , 1998 that has shown enhanced neuronal responses around the rhinal sulci for remembered items that had to be selected for a response, and similar single unit responses have been reported in perihirnal cortex (Lehky and Tanaka, 2007). Activity in the parahippocampal gyrus has also been observed in functional MRI studies in humans assessing WM biases of visual attention Grecucci et al, 2010) and in visual perceptual tasks (Murray and Richmond, 2001;Buckley and Gaffan, 2006;O'Neil et al, 2009).…”
Section: Discussionmentioning
confidence: 88%
“…For example, recent neuropsychological studies have revealed that selective bilateral HC damage impairs recognition memory (Bird et al, 2007), discrimination learning , and odd-one-out decisions (Lee et al, 2005a) for scene, but not face, stimuli. In contrast, larger MTL lesions that encompass both the HC and PrC result in poor long-term memory for scenes and faces (Taylor et al, 2007) and reduced discrimination accuracy for scenes, faces, and objects Lee et al, 2005b).…”
Section: Introductionmentioning
confidence: 99%